Manajemen risiko pada bank syariah: strategi kepatuhan terhadap prinsip syariah - Lamondo, Mohamad Safriyanto (Maliki Interdisciplinary Journal, 2025)
This article examines risk management strategies in Islamic banking with a focus on compliance with Islamic principles. In practice, Islamic banks face unique challenges due to the limited use of conventional financial instruments that contain elements of riba, gharar, and maysir. This study uses a descriptive qualitative approach to explore how risk management is implemented within the Islamic framework, as well as how the roles of the Islamic Supervisory Board (SSB), Islamic audit, and corporate governance support such compliance. The results of the study indicate that Islamic risk management strategies not only function as a tool for mitigating financial risk, but also as a form of mandate and moral responsibility in maintaining the integrity of Islamic finance. This study emphasizes the importance of strengthening human resource capacity, innovation of Islamic financial products, and utilization of technology to support transparency and efficiency of the risk management system.